Effects of the Singapore government's intervention on the spread of COVID-19: an econometric approach - Tay, Alvyn Jun Le (Nanyang Technological University, 2022)
This paper seeks to combine various important government intervention policies to analyse the effects and identify the significant intervention determinant that affects the (i) domestic COVID-19 infection and (ii) COVID-19-related ICU admittance. There is currently a lack of existing literature attempting to combine multiple intervention strategies utilising data from both non-pharmaceutical interventions (NPIs) and pharmaceutical interventions (PIs) to identify the most prevalent measure affecting the spread of COVID-19. Hence, this study attempts to bridge the abovementioned research gap by using the following policy measures: Dose 1, Dose 2, Booster, Safe Management Measures (SMM), Vaccinated-Differentiated Safe Management Measures (VDS) and Home Recovery Programme (HRP). Using daily data from 7 April 2020 to 31 December 2021 gathered from the Ministry of Health and Government of Singapore database, our empirical evidence identified stringent NPI policies and high percentage of population that have completed two doses to have significant and negative impact on infections and ICU admittance due to COVID-19. While relaxed NPI polices have significant and positive impact on infections and ICU admittance due to COVID-19. The findings demonstrate the success of the Singapore government’s efforts in encouraging a high vaccination rate in our population and identified that despite the gradual relaxation of restriction measures, being fully vaccinated with 2 doses reduces the number of COVID-19 infections and remains a vital factor. The first policy implication of our findings encourages governments of countries (which still have low rates of vaccination) with the need to step up their measures in encouraging vaccination, while the second policy implication informs policymakers not to downplay the spike of infections that come from relaxation of NPIs.